IFRS convergence and earnings forecasts: Malaysian IPO companies - Zulaikha Rabitah, Zaidi (2014)
The study sheds light on the Malaysian initial public offering (IPO) management earnings forecasts by examining the effect of International Financial Reporting Standards (IFRS) convergence and the forecast errors. It examines whether the convergence of IFRS is a credible signal of improved quality of financial information. Besides, the study also investigates the other factors that influence the forecast errors of the earnings forecasts. A sample of 98 IPO companies that went public during the period 2004-2007 is used. The time frame of this study includes the years 2004 to 2005 (i.e., pre-IFRS convergence) and years 2006 to 2007 (i.e., post-IFRS convergence). Forecast errors as a dependent variable is used to proxy the earnings forecast error and to represent financial disclosure quality. By examining the forecast errors in two different periods (i.e., pre-IFRS convergence & post-IFRS convergence), the study finds that the forecast errors has increased under the post-IFRS convergence. In addition, the findings reveal the size of the company is significantly negative with the forecast errors. This study has implications on the disclosure regulations of earnings forecasts in the prospectuses in Malaysia and provides evidence regarding disclosure of the earnings forecasts being changed from mandatory to voluntary in Malaysia.